ASSESSING TEACHERS’ PREFERENCE TOWARDS TEXTBOOKS PROVIDED BY PRIVATE-SECTOR PUBLISHERS - Nabilla Ulayya Musyafa; Slamet Riyadi; Novita Pri Andini (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2024)
This study aims to investigate the factors influencing English teachers’ preferences for textbooks provided by private-sector publishers, with a focus on teachers in SMP 09 Tegal, Indonesia. The importance of textbooks in the teaching-learning process is crucial, as well as selecting appropriate textbook used in the classroom. Despite the availability of textbooks from both government and private-sector publishers, there is limited research on teachers’ preferences in this context. This qualitative study employs a phenomenological approach that involves in-depth interviews and observations of English teachers and students at SMP N 09 Tegal. Participants included three experienced English teachers and one chairman of the MGMP Bahasa Inggris (English Teacher Forum), as well as three students selected through purposive sampling. Data were collected and analyzed thematically to uncover the underlying factors influencing textbook selection, teachers’ perception towards the use of private-sector publisher’s textbook, and challenges in the use of textbook by private-sector publisher’s textbook. The findings reveal that content quality and variety, including the incorporation of practice questions and visual media, are significant factor in teachers’ textbook preferences. Teachers also value textbooks’ usability, practicality, readability, and the availability of supplementary materials. Despite generally positive perceptions of textbook by private-sector publisher, several challenges have been identified., such as language and content complexity, lack of local context, and infrastructure limitations. Student related challenges include diverse characteristics and varying levels of English proficiency that needs adaptable teaching strategies from teachers. Therefore, this study suggests that government through Ministry of Education, Culture, and Research can make textbook that better suits the needs of students and teachers in the classroom in order to benefit Indonesian education in general. Keywords: challenges, English teachers, private-sector publishers, teachers’ perceptions, teachers’ preference.